EVOLUTION OF C-CO2 IN SOILS OF DIFFERENT ECOSYSTEMS IN THE ALTO ACRE REGION, ACRE, BRAZIL - de Farias , Maria Aparecida Barros Mota; de Oliveira, Janiffe Peres; Hoffmann, Ricardo Bezerra; da Silva , José Márcio Malveira; Dias, Sileno; Beber , Paulo Márcio; da Silva, Maralina Torres; Oliveira, Deborah Virgynia Cardoso de Freitas (Seven Editora, 2024)
Different studies, developed over the years, have shown that the increase in human activities on the soil can influence the release of gases related to the increase in the greenhouse effect. In this sense, the use of methods that evaluate the evolution of C-CO2 has been considered as important indicators to detect changes in the environment, since they can be influenced by the crop and its cultivation system as a result of impacts on microbial activity. The objective of this work was to evaluate the release of C-CO2 from soils submitted to different ecosystems. Laboratory tests were carried out where soil samples, submitted to five different ecosystems, were collected in three different periods throughout the year in the municipalities of Brasiléia and Epitaciolândia, Alto Acre region, in the state of Acre, and were subsequently incubated. Subsequently, the evolution of C-CO2 was evaluated, and the readings were carried out periodically until the 500th day of incubation of the samples. The data were analyzed in order to evaluate the effect of different plant species on the evolution of C-CO2. Regarding the collection carried out in April, there was no difference in the evolution of C-CO2 between the areas. However, in the month of June, which comprises the period of the beginning of the transition between the rainy season and the dry season, and in the month of August, the dry season, it was observed that in the area of native forest occurred the highest values of C-CO2 flux, differing statistically from other areas within these months of collection. Between the collection times, only in the area of agroforestry system no significant differences were recorded in the evolution of C-CO2. The highest accumulated values of C-CO2 were recorded in the following sequence: native forest > agroforestry system > area with cassava > cultivated pasture > area with banana. It is concluded that the areas that present a greater contribution of plant material to the soil can serve as a stimulus to the development of microorganisms that, consequently, increase the flow of CO2, especially until the beginning of the dry season and that the absence of moisture negatively influences the emission of C-CO2, causing significant differences in the amount of release of C-CO2 between the study areas at the same time of evaluation.      DOI:https://doi.org/10.56238/sevened2024.037-036